Peer Counseling untuk Meningkatkan Self Efficacy terhadap Perilaku Berisiko pada Remaja Kelas XI TKJ 1 SMK Negeri 6 Malang Tahun Pelajaran 2021/2022 - Etik Fariati (Departement of Mathematics Education, 2023)
This research is motivated by the increasing number of cases showing an increase in risky behavior syndromes among adolescents, including pregnancies outside of marriage, juvenile crime, and drug abuse. One of the efforts to overcome risky behavior syndrome is through peer counseling. This counseling is seen as quite effective because it fosters self-efficacy from and for adolescents towards risky behavior. Adolescent self-efficacy towards risky behavior is the adolescent's belief in being able to refuse risky behavior. The purpose of this study was to prove the effectiveness of peer counseling in increasing adolescent self-efficacy towards risky behavior. This article is anaction research. The focus of this research lies in the actions that will be carried out in class XI TKJ 1 students of SMK Negeri 6 Malang in the form of peer counseling in an effort to increase adolescent self-efficacy towards risky behavior. This research was conducted at SMK Negeri 6 Malang. The subjects of this study were 5 students who participated as peer counselors and 30 students of class XI TKJ 1 who were given peer counseling. Data collection methods in this study were questionnaire methods (pre-test and post-test), focus group discussion, and observation. The results showed that there was an increase in the self-efficacy of the research subjects in terms of their cognitive, motivational, affective and behavioral tendencies.